Pseudomonas aeruginosa Detection Using Conventional PCR and Quantitative Real-Time PCR Based on Species-Specific Novel Gene Targets Identified by Pangenome Analysis - Chufang Wang; Chufang Wang; Qinghua Ye; Aiming Jiang; Jumei Zhang; Yuting Shang; Fan Li; Baoqing Zhou; Xinran Xiang; Qihui Gu; Rui Pang; Yu Ding; et al. (Frontiers in Microbiology)
Mining novel specific molecular targets and establishing efficient identification methods are significant for detecting Pseudomonas aeruginosa, which can enable P. aeruginosa tracing in food and water. Pangenome analysis was used to analyze the whole genomic sequences of 2017 strains (including 1,000 P. aeruginosa strains and 1,017 other common foodborne pathogen strains) downloaded from gene databases to obtain novel species-specific genes, yielding a total of 11 such genes. Four novel target genes, UCBPP-PA14_00095, UCBPP-PA14_03237, UCBPP-PA14_04976, and UCBPP-PA14_03627, were selected for use, which had 100% coverage in the target strain and were not present in nontarget bacteria. PCR primers (PA1, PA2, PA3, and PA4) and qPCR primers (PA12, PA13, PA14, and PA15) were designed based on these target genes to establish detection methods. For the PCR primer set, the minimum detection limit for DNA was 65.4 fg/μl, which was observed for primer set PA2 of the UCBPP-PA14_03237 gene. The detection limit in pure culture without pre-enrichment was 105 colony-forming units (CFU)/ml for primer set PA1, 103 CFU/ml for primer set PA2, and 104 CFU/ml for primer set PA3 and primer set PA4. Then, qPCR standard curves were established based on the novel species-specific targets. The standard curves showed perfect linear correlations, with R2 values of 0.9901 for primer set PA12, 0.9915 for primer set PA13, 0.9924 for primer set PA14, and 0.9935 for primer set PA15. The minimum detection limit of the real-time PCR (qPCR) assay was 102 CFU/ml for pure cultures of P. aeruginosa. Compared with the endpoint PCR and traditional culture methods, the qPCR assay was more sensitive by one or two orders of magnitude. The feasibility of these methods was satisfactory in terms of sensitivity, specificity, and efficiency after evaluating 29 ready-to-eat vegetable samples and was almost consistent with that of the national standard detection method. The developed assays can be applied for rapid screening and detection of pathogenic P. aeruginosa, providing accurate results to inform effective monitoring measures in order to improve microbiological safety.